IRT Method for Measuring The Quality of High School Mathematics Mid-Semester Assessment Questions in Magelang - Gunawan; Hidayati, Kana (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
Learning assessment is an important part of the learning process. The quality of the assessments carried out must of course be proven, namely by using item analysis, one of which is analysis using the IRT (Item Response Theory) method. This research aims to determine the quality of the question items that have been designed in mathematics mid-semester assessment questions using the IRT method. The method used in this research is descriptive analysis with a quantitative approach. The research subjects were 143 class XI students at one of the Magelang Regency high schools. The research instrument used was mathematics mid-semester assessment questions in Multiple Choice form, totaling 20 questions. Data analysis was carried out using the technique of analyzing the characteristics of the questions based on the IRT method, consisting of two stages, namely the assumption test and the analysis test. Based on the results of the analysis, it was found that the items met the assumption tests, namely the unidimensional, local independence, and invariance tests. Based on the model suitability test, a 2-PL model was obtained that was suitable for use, namely analyzing the different power parameters and the difficulty level of the questions. Based on the results of the estimation analysis on the question item parameters, it was concluded that 16 questions met the criteria for good quality questions and 4 questions that met the criteria for deficient questions.